Senior Management Control of Computer-Based Information Systems./ Criteria for Management Control Systems (Book). - Bouwman, Marinus J.; Hendrickson, Harvey S. (The Accounting Review, 1985)
Reviews two books "Senior Management Control of Computer-Based Information Systems," by Robert K. Mautz, Alan G. Merten and Dennis G. Severance and "Criteria for Management Control System," by R.K. Mautz and James Winjum.